Limites à eficiência técnica no modo de trabalho artífice: um estudo de caso - Oliveira, Daniela Lopes de (2023)
For most of human history, craftsmanship was the dominant way of production, however, it was gradually replaced by mechanized activities after the industrial revolution. Therefore, the current context is characterized by mastery of technique, configuring the dominant logic based on maximum efficiency. However, the prevailing organizational model has shown relationships with environmental problems and social issues. Thus, to contribute to approaches that study alternative ways of work and organization, it is proposed to investigate the craftsman’s way of work. Therefore, this study has the general objective of analyzing how the craftsman responds to the tensions established between the limits of his way of working, which is based on manual work, and the dominant logic of production, based on maximum technical efficiency. To collaborate with the research’s question, the following specific objectives were observed: to characterize the craftsman’s work, to identify the tensions of the craft in relation to the way of working guided by maximum technical efficiency and the description of how the craftsman responds to the demands of efficiency in front of the limits of their production way. The theoretical framework considers the modern concept of technique in Jacques Ellul, rescues the definition of craftsman work addressed by Richard Sennett, presents the question of the limits that permeate craftsmanship, and, finally, brings studies about how some contemporary craftsmen are responding to the demands of the current work context. Therefore, this research followed a qualitative approach of exploratory-descriptive nature of inductive character, outlined by a case study. Data were analyzed qualitatively, allowing recognition of the limits present in the handcrafted production mode and the tensions that permeate the craft. The main tension observed is related to the need to be a salesperson and manage a small business. Thus, the pressure for efficiency is tangential to manual activity and materializes in sales and management activities. Luxury marketing is observed as an element that configures the craftsman’s response to the logic of technical efficiency. In addition, the craftsman converts some of the trade limits into a selling point. Another tension point highlighted by the study is the craftsman’s relationship with social media. Despite maintaining the essential characteristics of manual crafts, the answer given by the craftsman shows that he needs to combine elements of conventional logic in order to remain in the market. Since he uses luxury marketing as an argument, the answer does not characterize an alternative because it does not offer opposition to capitalism.